Experiencing speech : a skills-based, panlingual approach to actor training - Caban, Andrea; Foh, Julie; Parker, Jeffrey (Jeffrey B.) (Routledge, 2021)
"Experiencing Speech: A Skills-Based, Panlingual Approach to Actor Training is a beginner's guide to Knight-Thompson Speechwork®, a method that focuses on universal and inclusive speech training for actors from all language, racial, cultural, and gender backgrounds and identities. This book provides a progression of playful, practical exercises designed to build a truly universal set of speech skills that any actor can use, such as the ability to identify, discern, and execute every sound found in every language on the planet. By observing different types of flow through the vocal tract, vocal tract anatomy, articulator actions, and how these components can be combined, readers will understand and recreate the process by which language is learned. They will then be introduced to the International Phonetic Alphabet (IPA) and will practice using the IPA for narrow transcription of speech sounds. The book also offers both an intellectual and physical understanding of oral posture and how it contributes to vocal characterization and accent work. This approach to speech training is descriptive, giving students a wide and diverse set of speech sounds and skills to utilize for any character in any project, and it establishes a foundation for future accent study and acquisition. Experiencing Speech: A Skills-Based, Panlingual Approach to Actor Training is an excellent resource for teachers and students of speech and actor training, as well as aspiring actors looking to diversify their speech skills"--